GAMBARAN RESISTIVITAS BATUAN BAWAH PERMUKAAN DAERAH INTURSI AIR LAUT (STUDI KASUS PULAU TERNATE) - Salam, Ramdani; Nagu, Nani; Lessy, Mohammad Ridwan; Achmad, Rahim (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2018)
The measurement of 2D geoelectrical using Wenner-Schlumberger configuration has been conducted, in order to know the distribution of seawater intrusion in each depth. The result inversion is showed the seawater intrusion untuil 20m depth. The measurement result of rock ressitivity ranging from 0-10 Ωm is salt water, for brackish water between 10 Ωm untill less than 30 Ωm and the value more than 30 Ωm is estimated as fresh water. Another measurements namely water quality of dug well also carried out to measure such as: Electrical Conductivity (mS/cm), Total Dissolved Solid (g/L) and Salinity (ppt). The dug wells which on a line with PDAM wells, have a high DHL, TDS and Salinity value. The value of water quality measured then presented as a map of sea water intrusion. The combination of methods reported here is very important to be applied at coast vurnarable to seawater intrusion